The Impact of Philology Practicum for Arabic Language and Literature Students on The Preservation of Ancient Manuscripts at Dayah Teungku Chiek Awe Geutah: Dampak Praktikum Filologi Mahasiswa Prodi Bahasa dan Sastra Arab Terhadap Pelestarian Naskah Kuno Di Dayah Teungku Chiek Awe Geutah - Sumardi; Zulhelmi, Anshar; Ahmad, Muhammad Yunus; Fajri, Akmal; Chairunnisa Ahsana Amalan Shaliha; Deskananda; Sofyan, Zulkhairi (Indonesian Journal of Islamic History and Culture, 2024)
This study aims to examine the impact of the preservation of ancient manuscripts from the Philology Practicum activities conducted by the students of the Arabic Language and Literature Program (BSA) at the Faculty of Adab and Humanities, UIN Ar-Raniry Banda Aceh, at Dayah Teungku Chiek Awe Geutah. The philology Practicum is a Compulsory course for BSA Students, making it an essential activity for them to undertake before completing their studies. This activity is expected to have a significant impact on students in preserving ancient manuscripts, which are important heritage, and also assist the heirs of Teungku Chiek Awe Geutah in maintaining and preserving these manuscripts. Based on these considerations, this study formulates the following research questions: 1) Why is the Philology Practicum course important for the preservation of ancient manuscripts at Dayah Teungku Chiek Awe Geutah. 2) What is the impact of the Philology Practicum activities on the preservation of ancient manuscripts at Dayah Teungku Chiek Awe Guetah? Using a descriptive qualitative methodology based on preservation theory with a literature study approach, the researchers conducted analysis and data collection through stages consisting of observation, interviews, documentation, and literature review. The data analysis was carried out in three stages: data reduction, data presentation, and conclusion drawing. The results obtained from this research are: 1) The Philology Practicum activities conducted by BSA students have a significant impact on the preservation of ancient manuscripts at Dayah Teungku Chiek Awe Guetah. 2) The Philology Practicum activities assist the heirs in identifying the manuscripts located ata Dayah Teungku Chiek Awe Geutah. 3) There are three obstacles faced by the heirs in preserving the manuscripts: human resources (HR), limited budget, and adequate facilities.